Short-Term Anterior Segment Changes After Nd-YAG Laser Posterior Capsulotomy in Pseudophakic Eyes with Fuchs’ Endothelial Dystrophy - Eleiwa T; Khedr NED; Fayek H; Bayoumy A (Clinical Ophthalmology, 2021)
Taher Eleiwa,1 Negm El-Din Khedr,1,2 Hytham Fayek,1 Ahmed Bayoumy1 1Department of Ophthalmology, Faculty of Medicine, Benha University, Benha, Egypt; 2Department of Ophthalmology, Mataria Teaching Hospital, Mataria, EgyptCorrespondence: Taher EleiwaDepartment of Ophthalmology, Faculty of Medicine, Benha University, 79 Nozha st, Heliopolis, 11341, Cairo, EgyptTel/Fax +20 1069901973Email Taher.eleiwa@fmed.bu.edu.egPurpose: To describe the changes in the central corneal thickness (CCT), endothelial cell count (ECC), intraocular lens (IOL) position, and refractive error 1 and 3 months after Nd-YAG laser posterior capsulotomy (YAG-PC) for posterior capsular opacification (PCO) in pseudophakic eyes with Fuchs’ endothelial cell dystrophy (FECD).Design: Prospective case-control.Participants: Fifty pseudophakic eyes of 50 patients with visually significant PCO (25 with healthy corneas, and 25 with FECD grade 1 and 2).Methods: FECD was clinically graded, and only patients without clinically evident corneal edema were included in the study (grade 1 and 2). All patients received YAG-PC and were followed up after 1 and 3 months. Best-corrected visual acuity, refractive errors, ACD, CCT, and ECC were assessed and compared between the pre-laser values and that of the 2 follow-up visits.Results: In both groups, BCVA showed significant improvement (P< 0.05). Compared to healthy controls, a significant hyperopic shift was observed in the FECD eyes at the 2 follow-up visits (P=0.027, and 0.019). A significant backward movement of the IOL was observed in the FECD eyes in the 2 follow-up visits (P=0.043, and 0.02). There was a significant correlation between the hyperopic shift in the FECD eyes and the ACD deepening during the 1st month (R= − 0.6, P=0.001) and 3rd month (R= − 0.4, P=0.04). Significant drop in the ECC was noted in both groups but without significant increase in the CCT.Conclusion: Compared to controls, a hyperopic shift and backward movement of the IOL were observed in the FECD eyes after YAG-PC. No significant corneal thickening was found in both groups despite the significant drop in the ECC. Future studies are required to confirm our results and monitor the long-term changes after YAG-PC in FECD.Keywords: YAG laser, posterior capsulotomy, Fuchs’ dystrophy, posterior capsular opacification